Design and development of a flying robot with improved time constant in rescue accident victims - Rashid, Muhammad Mahbubur; Molik, Md. Sazib; Rahman, Mohammed Ataur (2014)
The goals of this flying robot are to provide an accurate and precise search, rescue, exploration and saving of accident victims and also to reduce rescue time constraint. The major task in designing this robot is able to recognize the human body figure and detect the temperature of human body while searching the victim. At first, the design of robot’s body will use base on coaxial helicopter. After that, system and recognition of human body figure system which uses the machine vision knowledge. Moreover, obstacles avoidance system, navigation system and flight level measurement system, communication system and temperature measurement system also included.